Measuring Critical Thinking Skills with Online Instrument in Circular Motion Concept - I Dewa Putu Nyeneng; Eko Suyanto; Doni Andra; Hanifah Nadia Elokanita (Berkala Ilmiah Pendidikan Fisika, 2022)
The critical thinking skills need to be possessed by every student, and its evaluation requires the right measuring tool., while the critical thinking assessment has not used the right instrument. This study aims to produce an instrument to measure critical thinking skills in a circular motion. The method using Research and Development assimilated from Gall, Gall, & Borg and Sugiyono, adjusting to the purpose and time, so the steps are 5. The R&D steps are research and information collection, planning, developing a preliminary form of product, limited field test, and product revision. The developed instrument consists of 10 conceptual essay questions. The result from expert validation of construction, substance, and language aspects is very valid in each aspect, with 86.1%, 81.7%, and 75%. The result from field testing in 32 students is tested with Anates software and has a reliability of 0.77 in a high category. The validity result gets eight valid questions. Those eight valid questions have discrimination power which is medium, good, and very good. The difficulty levels are medium and hard. The average value of the student's score on the instrument is 43.69 shows that the students have medium skills of critical thinking in a circular motion. This study implies that the final product of the instrument consists of eight conceptual essay questions in the google form.